Penggunaan Diapers Selama Masa Toilet Training dengan Kejadian Enuresis pada Anak Prasekolah - Tri Ratnaningsih; Novia Eka Putri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to analyze the relationship between the use of diapers during toilet training and the incidence of enuresis in preschool children in RA Al Hidayah 1 & 2 Sidoarjo Regency, East Java. The research design used in this study is the correlation analytic design using a cross sectional approach. The results showed that almost half (48.9%) of respondents who never used diapers during the toilet training period did not experience enuresis. Conclusion, children who were not applied diapers during the toilet training period did not experience enuresis and children who were put on diapers tended to experience enuresis. Keywords: Diapers, Enuresis, Preschool, Toilet Training